Cell biology : A laboratory handbook; VOL.1 - Celis, J. E; Ed (Academic Press, 2006)
A three volume laboratory guide providing protocols for basic and advanced cell biological techniques. The text includes nearly 200 articles ranging from general procedures for tissue culture to phosphopeptide mapping. Lists for reagents, media, cell lines and suppliers are also provided.